BUILDING A GENERATION OF EDUCATION DURING THE COVID 19 PANDEMI - Sari Ayu Wahyu Br Brutu; Rizky Adinda; Nuraini Nindra Utami Trg; Nurhayati Nurhayati; Mavianti Mavianti (Proceeding International Seminar of Islamic Studies, 2021)
During the Covid Pandemic, based on the reflections held by educators and students. Research departs from the concept to fequit able education,where education during this pandemic has the potential as a model of equitable education. This research was conducted through had escriptive quantitative approach. This Study uses primary data in the formof samples taken by accindental sampling and secondary data in the form of predecess or studies. The finding sex plain that the conditionof Facilities and Infrastructure by Students and Theachers is sufficient to describe ethereadiness of implementing and Building the current Generation of Eduacation. However, this learning mainly has obstacles, namely not being able to meet face to face directly However, a strong determination to build a Generation of Eduaction is ready to be implemented properly and corectly. Therefore, synergy between Students, Theachers, Educational Institutions, and the governmentis meeded fo fix the Learning system so that it runs more evenly,in accor dancew it he ducation, by the goal of Building a Generation of Education during the Covid 19 pandemic.